The Role of Financial Development in Poverty and Income Distribution Dynamics in ASEAN Countries: A Panel Cointegration Analysis - Soh, Tuan Muhammad Amir Amirul Tuan; Zainuddin, Muhamad Rias K. V.; Mohamad, Abdul Hayy Haziq; Arifin, Arifin; Azam, Abdul Hafizh Mohd (International Journal of Economics and Financial Issues, 2025)
The objective of this study is to examine the impact of financial development on income equality and poverty reduction in selected Southeast Asian countries. This study utilizes the Panel Autoregressive Distributed Lag (Panel ARDL) method. In addition, the researcher also used the statistical descriptive method, the unit root test method to measure the stationarity of variables, and the cointegration panel method to measure the cointegration between the dependent variable and the independent variable. The results of the study obtained from the panel analysis found that financial development can reduce income inequality in selected ASEAN countries, but there is no implication for poverty. For the short run ARDL results in each country, financial development has a positive impact on poverty for Indonesia and Singapore and can reduce the income gap for Singapore and Thailand. However, the findings for Philippines show that financial development exacerbates income inequality and poverty. Finally, the role of the government and the central bank in each ASEAN country is very important in ensuring that financial development can have a positive impact on poverty reduction and income equality for ASEAN countries.